Faktor-Faktor yang Mempengaruhi Resiliensi pada Remaja di Pondok Pesantren: Scoping Review - Atiqur Rohman; Willi Holis; Ahmad Zaini Arif (Indonesian Health Science Journal, 2025)
Introduction: Adolescence is a crucial period in individual development, characterized by biological, psychological, and social changes. The transition to boarding schools, such as Islamic boarding schools, presents adolescents with new challenges that may affect their well-being. Objective: This study aims to identify factors influencing adolescent resilience in Islamic boarding schools using the scoping review method. Methods: The literature search was conducted using the PubMed, ScienceDirect, Scopus, and Google Scholar databases, guided by the Arksey and O’Malley framework and the PRISMA-ScR guidelines. This process was complemented by the development of inclusion and exclusion criteria. The inclusion criteria applied in this study were as follows: original research articles published in English, within the last five years (2020–2024), available in full-text format, accessible, and specifically discussing resilience among adolescents in Islamic boarding schools. Results: A total of seven articles with similar themes indicated that adolescent resilience in boarding schools is influenced by various factors, including social support, coping strategies, and biopsychosocial aspects. Support from family, peers, and caregivers plays a vital role in building psychological resilience. Adaptive coping strategies, such as emotion regulation and seeking social support, help adolescents manage academic and social pressures. Additionally, biopsychosocial factors, such as physical activity, personality, and life experiences, contribute to strengthening resilience. Conclusions: This study concludes that a combination of social support, appropriate coping strategies, and biopsychosocial balance plays a crucial role in fostering adolescent resilience in Islamic boarding schools. These findings are expected to serve as a foundation for developing strategies to enhance adolescent well-being and mental resilience in boarding school environments.